2020
DOI: 10.1016/j.ebiom.2020.103146
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a real-time artificial intelligence-assisted system for detecting early gastric cancer: A multicentre retrospective diagnostic study

Abstract: Background We aimed to develop and validate a real-time deep convolutional neural networks (DCNNs) system for detecting early gastric cancer (EGC). Methods All 45,240 endoscopic images from 1364 patients were divided into a training dataset (35823 images from 1085 patients) and a validation dataset (9417 images from 279 patients). Another 1514 images from three other hospitals were used as external validation. We compared the diagnostic performance of the DCNN system wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 18 publications
(7 reference statements)
0
38
0
Order By: Relevance
“…Based on the full-text review, we excluded eight more studies because they were not in adherence with our inclusion criteria. Finally, 15 studies met all inclusion criteria [ 6 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The flow diagram of the systematic search is presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the full-text review, we excluded eight more studies because they were not in adherence with our inclusion criteria. Finally, 15 studies met all inclusion criteria [ 6 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. The flow diagram of the systematic search is presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Our study findings demonstrate that the CNN model can improve the detection performance of EGC, which is higher than that of endoscopists. Tang et al [ 35 ] reported that the detection performance of EGC is even higher when endoscopists use the CNN model ( Table 4 ). Obtaining high-quality images to detect EGC is difficult, especially for inexperienced endoscopists.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, we only included images with histologically proven malignancy, indicating the system could not be used to differentiate malignant lesions from non-cancer mucosa. We have established an AI system in detecting early gastric cancer from non-cancer mucosa in our previous report (30). The two systems can be used together to detect early gastric cancer lesions from non-cancer mucosa first and then differentiate intramucosal GC from advanced lesions, thus may facilitate the endoscopic treatment of GC.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of included studies were graded as low quality, mainly due to the high risk of selection bias in the training or validation sets and for the lack of clinical real-time validation. Therefore, Tang et al [ 43 ] developed and validated a real-time DL-CNN system for detecting EGC that confirmed high accuracy rates of AI with sensitivity, specificity, and the AUC ranging from 85.9% to 95.5%, 81.7–90.3%, and 0.887–0.940, respectively. Finally, Wu et al [ 44 ] carried out a multicenter, randomized, controlled trial using a deep-learning CNN and deep reinforcement-learning system named “ENDOANGEL”.…”
Section: Upper Gastro-intestinal Tractmentioning
confidence: 94%